Innovative Technologies in Management and Science - Klempous, Ryszard; Nikodem, Jan (Topics in Intelligent Engineering and Informatics,, 2015)
This carefully edited book presents recent research in Innovative Technologies in Management and Science, representing a widely spread interdisciplinary research area with many applications in various disciplines including engineering, medicine, technology, or environment, among others. It consists of eleven invited and scholarly edited chapters written by respectable researchers and experts in the fields that integrate ideas and novel concepts in Intelligent Systems and Informatics. Most of the chapters were selected from the initial contributions to the World of Innovation Conference held on April 3, 2012 in Wroclaw, Poland. The contributions are focusing on research and development of the latest IT technologies, in the field of Cloud Computing, IT modeling, as well as optimization problems. The chapters presented can be grouped into three categories: Innovation supported by Clouds Technology, Innovation proposals in management area, and Theoretical refinement for innovative solutions.  .